Organic fertilizer-mediated assembly of rhizosphere core microbiota contributes to increased sugarcane productivity - Deng, Jun; Zhang, Zhongfu; Wang, Yutong; Ai, Jing; Zhao, Yong; Li, Bao; Li, Hongjun; Deng, Yan; Zhang, Fusuo (Frontiers in Plant Science, 2026)
Optimizing fertilization strategies to enhance crop yield remains a critical challenge in sustainable agriculture. In this study, two field experiments were conducted in Yunnan Province, China, to evaluate the effects of three fertilization regimes—no fertilization (CK), chemical fertilization (F), and combined chemical and organic fertilization (FM)—on sugarcane yield, soil biochemical properties, and rhizosphere bacterial communities. The results showed that the FM treatment significantly increased sugarcane yield at both sites compared to CK and F. This yield improvement was accompanied by increased soil nutrient availability, enhanced enzyme activities, and significant changes in microbial community structure. High-throughput 16S rRNA sequencing results indicated that the FM treatment selectively enriched specific taxa, such as Actinobacteriota and Proteobacteria, and promoted the development of a more modular and stable microbial co-occurrence network. Correlation analysis and structural equation modeling further revealed that the FM treatment improved sugarcane yield primarily through microbiome-driven pathways that indirectly enhanced soil biochemical functions. Overall, this study unveils the mechanistic links between integrated fertilization strategies, rhizosphere microbial network stability, and sugarcane yield, providing scientific evidence for sustainable fertilization management in sugarcane production systems.